Synthesis of nanostructured titanium dioxide using recombinant protein templates - Chan, Yong Rong (2016)
Titanium dioxide nanoparticles are widely used in a variety of applications, for instance in the environmental and energy field, chiefly due to its high performing photocatalytic properties. The development and cost of new performance materials are largely determined by the synthetic approaches being exploited. Several studies have been published on the synthesis of titanium dioxide nanoparticles using conventional methods such as sol-gel and hydrothermal processes. However, efficacious studies in the synthesis of inorganic nanoparticles via the biomimetic approach have not been fully explored or understood. Furthermore, biomimetic synthesis possesses major advantages over other approaches and should therefore be further studied. These advantages include its good control of particles and shapes, the ability to be performed under milder conditions, as well as the minimization of adverse environmental effects. As such, this study sought to devise a single process for preparing nanostructured titanium dioxide material that contains both favourable morphological properties and crystal phases via a biomimetic approach. The first phase of this project involved the synthesis of ELK16-HIS and ELK16-FLAG recombinant protein templates via inverse thermal cycling (ITC), followed by the synthesis of titanium dioxide on the protein template base with a benchmarked concentration of 1:1 molar ratio. Annealing was subsequently conducted under argon atmosphere with respective temperatures of 623 K and 873K for 2 hours. Shape- and size-controlled titanium dioxide nanoparticles were readily obtained through this process. It was found that the complementary amino acid sequence on the template had desirable morphological control effects on both the size and shape of the titanium dioxide nanoparticles produced. A possible reason for such precise control over the morphology could be explained by the adsorption of amino acids on the growing surfaces of the nanoparticles, which led to the growth in selective planes direction. Rod and plate-like shaped titanium dioxide were selectively formed in the presence of histidine tag, glycine and aspartic acid. In summary, the bio-mimetic synthesis was shown to be a promising approach for the fabrication of nanostructured inorganic devices.